Report on CIAT's involvement in the Colombian Roundtable for Sustainable Cattle Production - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2019)
CIAT continued its strong involvement in the Colombian Roundtable for Sustainable Cattle Production (Mesa de Ganadería Sostenible, MGS) during 2020. Apart from joining the regular monthly meetings, CIAT also helped in the strengthening and further establishment of regional roundtables in the principal cattle regions of Colombia (now there exist 12 of them), supported the MGS leadership in inviting new members to the MGS (now more than 50 members, stronger involvement from the private sector), and participated in/facilitated several workshops around sustainable cattle production and value chains. CIAT also helped in facilitating the search for financial resources for operating the MGS in 2019 and beyond, which resulted in the obtainment of funds for a technical secretary during 2019 through Solidaridad Network and the Global Green Growth Institute (GGGI). One highlight from 2019 was the finalization of technical guidelines for the formulation of a national level policy for sustainable cattle production in Colombia and a first draft of the policy itself, which was submitted to the Colombian Ministry of Agriculture for evaluation. We are confident that the policy will be released during 2020.